Two-photon polymerization enabled multi-layer liquid crystal phase modulator. Issue 1 (December 2017) - Lee, Yun-Han; Franklin, Daniel; Gou, Fangwang; Liu, Guigeng; Peng, Fenglin; Chanda, Debashis; Wu, Shin-Tson
Abstract The performance of liquid crystal (LC) spatial light modulators depends critically on the amount of cumulative phase change. However, for regular phase modulators, a large phase change comes with a slow time response penalty. A multi-layer liquid crystal (LC) spatial light modulator offers a large phase change while keeping fast response time due to the decoupling between phase change and time response through engineered sub-micron scaffold. Here, we demonstrate specially designed 2- and 3-layer LC cells which can achieve 4 times and 7 times faster response time than that of conventional single-layer LC phase modulator of equivalent thickness, respectively. A versatile two-photon laser lithography is employed for LC cell scaffolding to accurately verify theoretical predictions with experimental measurements.